Tolerance of Ruppia sinensis Seeds to Desiccation, Low Temperature, and High Salinity With Special Reference to Long-Term Seed Storage - Gu, Ruiting; Zhou, Yi; Song, Xiaoyue; Xu, Shaochun; Zhang, Xiaomei; Lin, Haiying; Xu, Shuai; Yue, Shidong; Zhu, Shuyu (Frontiers in Plant Science, 2018)
Seeds are important materials for the restoration of globally-threatened marine angiosperm (seagrass) populations. In this study, we investigated the differences between different Ruppia sinensis seed types and developed two feasible long-term R. sinensis seed storage methods. The ability of R. sinensis seeds to tolerate the short-term desiccation and extreme cold had been investigated. The tolerance of R. sinensis seeds to long-term exposure of high salinity, cold temperature, and desiccation had been considered as potential methods for long-term seed storage. Also, three morphological and nine physiological indices were measured and compared between two types of seeds: Shape L and Shape S. We found that: (1) wet storage at a salinity of 30–40 psu and 0°C were the optimal long-term storage conditions, and the proportion of viable seeds reached over 90% after a storage period of 11 months since the seeds were collected from the reproductive shoots; (2) dry condition was not the optimal choice for long-term storage of R. sinensis seeds; however, storing seeds in a dry condition at 5°C and 33 ± 10% relative humidity for 9 months had a relatively high percentage (74.44 ± 2.22%) of viable seeds, consequently desiccation exposure could also be an acceptable seed storage method; (3) R. sinensis seeds would lose vigor in the interaction of extreme cold (-27°C) and desiccation; (4) there were significant differences in seed weight, seed curvature, and endocarp thickness between the two types of seeds. These findings provided fundamental physiological information for R. sinensis seeds and supported the long-term storage of its seeds. Our results may also serve as useful reference for seed storage of other threatened seagrass species and facilitate their ex situ conservation and habitat restoration.